Service optimalization for laboratory of metal working engineering by utilizing information and communication technology - Hendri Sulistyo; Mutaufiq Mutaufiq; Cahyo Puji Asmoro; Ricky Cahyasari Putra (Labor Dasar dan Sentral Universitas Andalas, 2021)
This study aims to optimize services in the laboratory by utilizing information and communication technology for all practicum requiring tools. The goal is to optimize services by developing lending and returning services using information and communication technology software. The method used is research and development by conducting experimental research and distributing questionnaires to students, technicians and educational laboratory administrators (PLP) of the use of information and communication technology. Optimization of laboratory services begins with the use of information and communication technology with the use of management information system software, then testing and applying conventional services compared to information and communication technology software in metalworking engineering laboratories. Furthermore, the service performance that has been applied is recorded and calculated to determine the optimization of changes in conventional services to information and communication technology. The questionnaire was distributed to get an assessment from users, namely students and PLP as materials for developing information and communication technology that had been used. The results of this research are 83.8% of the time efficiency of information tool services from conventional services to information and communication technology for the search for 5 tools. Equipment borrowing efficiency is 45% and tool return efficiency is 48.5%. Thus, the use of information and communication technology is optimal for use in practicum laboratories.